Fluid Balance Predicts Need for Intubation in Subjects With Respiratory Failure Initiated on High-Flow Nasal Cannula - Varipapa, Jr, Robert J; DiGiacomo, Erik; Jamieson, Daniel B; Desale, Sameer; Sonti, Rajiv (Respiratory care, 2021)
High-flow nasal cannula (HFNC) has gained widespread use for acute hypoxemic respiratory failure on the basis of recent publications that demonstrated fewer intubations and perhaps lower mortality in certain situations. However, a subset of patients initiated on HFNC for respiratory failure ultimately do require intubation. Our goal was to identify patient-level features predictive of this outcome. This was a retrospective cohort study of subjects with hypoxemic respiratory failure treated with HFNC. Individuals were described as having succeeded (if weaned from HFNC) or failed (if they required intubation). A variety of easily measurable variables were evaluated for their ability to predict intubation risk, analyzed via a multivariate logistic regression model. Of a total of 74 subjects, 42 succeeded and 32 failed. The mean ± SD net fluid balance in the first 24 h after HFNC initiation was significantly lower in the success group versus the failure group (-33 ± 80 mL/h vs 72 ± 117 mL/h; < .01). An adjusted model found only fluid balance and the previously described respiratory rate (breathing frequency [f]) to oxygenation (ROX) index ([[Formula: see text]/[Formula: see text]]/f) at 12 h as significant predictors of successful weaning (negative fluid balance adjusted odds ratio 0.77 [95% CI 0.62-0.96] for -10 mL/h increments [ = .02]; ROX adjusted OR 1.72 [1.15-2.57], < .01). A negative fluid balance while on HFNC discriminated well between those who required intubation versus those who were successfully weaned.